Sampling optimization for biomonitoring metal contamination with marine macroalgae. (December 2019) - García-Seoane, R.; Fernández, J.A.; Varela, Z.; Real, C.; Boquete, M.T.; Aboal, J.R.
Abstract: The aim of the present study was to optimize the protocol for sampling marine macroalgae to be used to biomonitor heavy metal contamination in marine ecosystems. For this purpose, we collected 50 subsamples of the brown seaweed Fucus vesiculosus at random in each of three sampling sites (SS) and determined the concentrations of Al, As, Cd, Co, Cr, Cu, Fe, Hg, N, Ni, Pb, Zn and δ 15 N. We used semivariograms to explore the possible existence of spatial structure in the concentrations of the elements. Spatial structure was observed in 88% of the semivariograms studied, with element concentrations varying longitudinally and transversally along the SS. Using randomization techniques, we estimated that in each SS, a minimum of 30 evenly distributed subsamples should be collected within three bands parallel to the coastline (and also at different heights on the rocks if necessary), and analyzed in a single composite sample representative of the intra-SS variability. Graphical abstract: Image 1 Highlights: Collecting ≥30 subsamples per site is recommended to represent the local variability. The position of the subsamples along the shoreline vertical position is important. Subsamples should be collected evenly distributed in 3 bands parallel to the shoreline. Abstract : Optimization of the macroalgae sampling protocol for its application in biomonitoring studies of heavy metal contamination in coasts.